PROPINA ENTRE DÁDIVA O BENEFICIO: FACTORES DETERMINANTES EN UN CONTEXTO FRONTERIZO - Ernesto Ortiz Tapia; Luis Fernando Maldonado Azpeitia; Carlos González Macías; Tomás Cuevas Contreras (European Scientific Journal, ESJ, 2015)
Tipping has become a unilateral gratification paid by the client reciprocating the service provider for a good service, to a moral obligation to a service that sometimes does not comply with quality standards. Even though it is true that in some countries the tip is mandatory based on a percentage of the account payable, regardless of the service received, in other countries it is not. However, in countries like Mexico it is customary to pay it based on a percentage and sometimes this percentage depends on the quality of the service received. Mexican legislation does not make tipping mandatory, but the border areas live in a mix of Mexican and American cultures and traditions, making tips a percentage of the consumption.